Characterizing agricultural impacts of recent large-scale US droughts and changing technology and management. (January 2018) - Elliott, Joshua; Glotter, Michael; Ruane, Alex C.; Boote, Kenneth J.; Hatfield, Jerry L.; Jones, James W.; Rosenzweig, Cynthia; Smith, Leonard A.; Foster, Ian
Abstract: Process-based agricultural models, applied in novel ways, can reproduce historical crop yield anomalies in the US, with median absolute deviation from observations of 6.7% at national-level and 11% at state-level. In seasons for which drought is the overriding factor, performance is further improved. Historical counterfactual scenarios for the 1988 and 2012 droughts show that changes in agricultural technologies and management have reduced system-level drought sensitivity in US maize production by about 25% in the intervening years. Finally, we estimate the economic costs of the two droughts in terms of insured and uninsured crop losses in each US county (for a total, adjusted for inflation, of 9 billion in 1988 and 21.6 billion in 2012). We compare these with cost estimates from the counterfactual scenarios and with crop indemnity data where available. Model-based measures are capable of accurately reproducing the direct agro-economic losses associated with extreme drought and can be used to characterize and compare events that occurred under very different conditions. This work suggests new approaches to modeling, monitoring, forecasting, and evaluating drought impacts on agriculture, as well as evaluating technological changes to inform adaptation strategies for future climate change and extreme events. Highlights: Models reproduce historical crop yield anomalies in US, perform better under drought. System-level drought sensitivity in US maize reduced 25. Total cost of direct crop losses from 2012 drought about 21.6 billion USD